Community-Based Tourism-Sustainable Development Strategy for Non Nuoc Cao Bang, Viet Nam - Cao Thi Thanh Phuong; Tran Thi Binh An; Tran Thi Kim Anh (Celebes Scholar pg, 2022)
Cao Bang province with the majestic and beautiful natural landscape is associated with the global geo-historical values, along with the value of biodiversity, the value of diversity of ethnic identity and the richness of culture and history with many national special relics and national relics have created a special attraction for Non nuoc Cao Bang Geopark to domestic and foreign tourists and become unforgettable tourist area. By means of observation, descriptive and comparative statistical analysis, the article focuses on discovering tourism potentials as well as learning about the development of community tourism in the Geopark of Cao Bang province, Viet Nam.